2021
DOI: 10.1093/jamia/ocab115
|View full text |Cite
|
Sign up to set email alerts
|

Patient portal engagement and diabetes management among new portal users in the Veterans Health Administration

Abstract: Objective The study sought to investigate whether consistent use of the Veterans Health Administration’s My HealtheVet (MHV) online patient portal is associated with improvement in diabetes-related physiological measures among new portal users. Materials and Methods We conducted a retrospective cohort study of new portal users with type 2 diabetes that registered for MHV between 2012 and 2016. We used random-effect linear reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
7
1
Order By: Relevance
“… 7 Aside from the benefits patients perceive, a growing body of research has shown that use of specific portal tools is positively related to certain health-related outcomes. Among patients living with diabetes, more months of portal use was related to improved hemoglobin A1c (HbA1c) and low-density lipoproteins control, 8 with earlier research showing that sustained use of the secure messaging tool among patients was related to controlled HbA1c among those who had uncontrolled HbA1c at baseline. 9 Similarly, in a sample of patients living with HIV (PLWH), use of the prescription refill tool was associated with changes in viral load from unsuppressed to suppressed over time.…”
Section: Introductionmentioning
confidence: 73%
“… 7 Aside from the benefits patients perceive, a growing body of research has shown that use of specific portal tools is positively related to certain health-related outcomes. Among patients living with diabetes, more months of portal use was related to improved hemoglobin A1c (HbA1c) and low-density lipoproteins control, 8 with earlier research showing that sustained use of the secure messaging tool among patients was related to controlled HbA1c among those who had uncontrolled HbA1c at baseline. 9 Similarly, in a sample of patients living with HIV (PLWH), use of the prescription refill tool was associated with changes in viral load from unsuppressed to suppressed over time.…”
Section: Introductionmentioning
confidence: 73%
“…We used data collected for a larger study performed between 2017 and 2020 examining patient portal use in diabetes management [ 5 , 12 , 13 ]. Participants included veterans with type 2 diabetes who had uncontrolled blood glucose (2012 mean HbA 1c >8.0% and less than 25% of the year with HbA 1c <8.0%), as well as repeated and current use of key portal features.…”
Section: Methodsmentioning
confidence: 99%
“…Study population, disease, controlled? Country, setting Author, year 0 (0) 7 ( 4) 30 (10) [76], 2021 a All studies are listed once in Tables 2-5 and are reported in the disease category of the condition that is most prominently investigated. We have included only the functionalities that the authors have reported in their articles.…”
Section: Study Design Burden Bmentioning
confidence: 99%